Organochlorines Pesticides in Sediments of Tigris River in Misan Governorate, Southern Iraq - Taban, Esraa A.; Farhan, Fadhil J.; Saleh, Salah M.; Shnaishel, Altaf R.; AL-Shammari, Mohammed H.; Al-Saad, Hamid T. (Mesopotamian Journal of Marine Sciences, 2025)
Pesticides are chemical compounds used worldwide for different purposes. These chemicals are well known for their long life, high toxicity, and slow degradation process. Many countries including Iraq banned the use of pesticides for their adverse effects. However, several pesticides are found incessantly in rivers. To highlight the recent situation of pesticide contamination in Tigris river at Misan governorate, southern Iraq. The study aims to determine the concentrations of selected organochlorine pesticide residues which are (Alpha lindane, Lindane, Delta-lindane, Heptachlor, Aldrin, Epoxy heptachlor, DDE, Dieldrin, DDD, Endrin aldehyde, Endrin ketone, Methoxychlor, Endrin, and Endosulfan) in the surface sediments of the ,Amara, Kumait ,Ali Al-Gharbi and Ali Al-Sharqi, four stations in Tigris Rivers at Misan Governorate, Iraq by using Gas Chromatography mass spectra .In general, higher total concentrations of organochlorine pesticide were found in the Amara station ( 17.05 µg/kg) and the lower organochlorine pesticides were found in the Ali Al Gharbi station (2.87 µg/kg).it is evident that the banned pesticides are used regularly by peoples and thus contaminating the environment. Therefore, the formulations of appropriate rules and their enforcement to control the manufacture and solicitation of such pesticides are an urgent need to save the environment. If we compare our data with other study its fules with these study in the area